Pengaruh Perbandingan Tepung Ketan (Oriza sativa L. Var glutinosa) dan Tepung Porang (Amorphophallus oncophyllus) Terhadap Karakteristik Lappet - Renty E.S.Lumbantobing; Suparthana, Putu; Ari Yusasrini, Ni Luh (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Lappet is a traditional food of the Batak Toba ethnic group characterized by a chewy texture. It is typically made from glutinous rice flour with unti filling, which consists of grated coconut mixed with palm sugar, shaped into a cone and wrapped in banana leaves. The nutritional content of lappet is predominantly composed of non-fiber carbohydrates. Porang flour has the potential to increase dietary fiber content and enhance the functional nutritional value of lappet. This study aimed to examine the effect of different proportions of glutinous rice flour and porang flour on the chemical and sensory characteristics of lappet and to determine the optimum ratio. The research was conducted using a Completely Randomized Design with treatments consisting of combinations of glutinous rice flour (%) and porang flour (%) arranged in five levels, namely P0 (100:0), P1 (90:10), P2 (80:20), P3 (70:30), and P4 (60:40). Each treatment was repeated three times, resulting in a total of 15 experimental units. The collected data were analyzed using analysis of variance, followed by Duncan’s Multiple Range Test (DMRT). The results indicated that variations in the proportion of glutinous rice flour and porang flour had a significant effect (P < 0.05) on moisture content, ash content, protein content, fat content, carbohydrate content, crude fiber, calcium oxalate levels, as well as sensory evaluation parameters including color,aroma, taste, texture, overall acceptability, and the scoring of lappet color and texture. The treatment using a 90:10 proportion of glutinous rice flour to porang flour (P1) produced lappet with the most optimal characteristics. The product contained 32.80% moisture, 0.46% ash, 3.20% protein, 9.82% fat, 53.87% carbohydrates, 1.82% crude fiber, and 0.003% calcium oxalate. From the sensory evaluation, the lappet was characterized by a light brown color and a chewy texture, while its taste and aroma were rated as favorable, resulting in a high level of overall acceptance among panelists.